Indonesia’s Tourism Economic Recovery Strategy through Meta-Green Business Initiatives Post-Covid 19 Pandemic - Ika Sri Hastuti; Melaty Anggraini (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study examines Indonesia’s tourism strategy after the Covid-19 pandemic. The Indonesian tourism sector has experienced a decline in economic income due to the Covid-19 pandemic. Tourism is the sector that mostly involves other economic sectors, such as hospitality, culinary, tour guides, and existing tourist attractions. Efforts to prevent the spread of the Covid 19 virus with the implementation of Large-Scale Social Restrictions (PSBB), it is necessary to close all tourist destinations. Post-pandemic or entering the "new normal after pandemic" which allows every country that has entered the green zone or entered a safe level and has successfully overcome the spread of COVID 19 to reopen its tourism sector with various rules imposed during the COVID-19 pandemic. Indirectly, the tourism sector needs to adapt by innovating to adapt to the conditions that are being faced and adapt to the unique behavior of the people who have changed due to the impact of the pandemic. changes in people’s behavior due to the impact of the pandemic in addition to complying with applicable health protocols also with the Meta verse concept approach which still prioritizes sustainable tourism economic efforts "Meta-Green Business Initiatives", this concept is expected not only to help restore the tourism financial strategy but also directly reduce the intensity of tourism. the spread of the Covid-19 virus by continuing to provide tourism services. The best for the wider community and reduce the impact of environmental issues by implication this concept in the tourism sector strategy during the "new normal after the pandemic"